Território e Aprendizagem, Espaço de Cultura e Cultura Popular - Guillermo Williamson; Adriano Nogueira (Universidade Estadual Paulista Júlio de Mesquita Filho, 2007)
Territorians are forms of learn. Can they be assumed into pedagogical efforts? When don't we dicotomize cultural and natural dimensions of human being? We do that trough an non-etnocentrical notion of curriculum.